The main directions, prospects and risks of the development of the system of settlement and financial relations in Russia in the context of the introduction of the digital ruble - N. A. Lazareva (Путеводитель предпринимателя)
The global changes that have taken place over the past three years in the world — a difficult epidemiological situation, strict quarantine restrictions, the development of a social digital platform have led to improvements in the system of providing financial services by banking structures. There is a transformation of traditional banking into financial and banking ecosystems. A number of countries are on the way to creating digital national currencies, the expert community is studying the issues of issuing digital money, and macroeconomic regulators are forming an assessment of positive expectations and negative consequences of the introduction of digital money.